Enablers for malaysian contractors to internationalise construction services - Hanid, Mahanim; Abdul Samad, Zulkiflee; Salleh, Hafez (2008)

(untitled)
Construction industry is a complex environment, unpredictable and full of uncertainties. The economic woes that take place in the late nineties have indeed dampened Malaysian construction industry. Projects are scarce and in order to survive, many construction companies seek for other alternative in order to remain in this industry. Thus, many took a brave step and venture upon overseas market. Due to this, research is carried out in order to identify problems that triggered Malaysian contractors to move into overseas market. Apart from that problems encountered in the foreign countries in which the construction companies are operating too are identified. With these objectives in mind, case studies are conducted in India and the Middle East to better understand the situation. Two notable Malaysian contractors companies point of view are taken into account regarding the case studies in which these companies are operating their projects there respectively. The findings from these interviews reveal the success factors of overseas ventures basically lies in the strategic marketing done by each construction companies. This is vital as it determines the company’s long term objectives.